Tata Kelola Kebijakan Dana Desa dan Partisipasi Kultural Masyarakat Desa di Kabupaten Boalemo - Tohopi, Rustam; Nani, Yacob Noho; Tui, Fenti Prihatini; Abdussamad, Juriko (Dynamics of Rural Society Journal, 2024)
The implementation of policies often encounters obstacles in its execution. One contributing factor is the lack of support, and policies are frequently met with resistance from the public. This often leads to failures in achieving policy goals and objectives. This study aims to identify forms of participation that are culturally rooted or emerge due to the local wisdom values held by the community. Through an in-depth examination of the coherence between policy values and social cultural values, empirical analysis is conducted using a qualitative approach based on the policy implementation model framework. To meet methodological standards, research data is analyzed through several stages: data presentation, data reduction, verification, and conclusion drawing. Data validity is ensured through data triangulation (sources and documents). The research findings indicate that village governments in Boalemo Regency have culturally coherent forms of participation related to the stages of Village Fund management policy. This participation involves "Mo'dulohupa Participation" in the policy planning stage, "Mo'huyula Participation" in the implementation stage, and "Mo'tahuli Participation" in the policy success evaluation stage. Despite being often overlooked, these forms of participation should be an integral part of decision-making regarding the governance of the Village Fund. Therefore, it is recommended that village governments in Boalemo Regency intensify the use of public participation forms, prioritizing the local wisdom of the Gorontalo region in the governance of the Village Fund, in all stages of policy planning, implementation, and evaluation, to achieve the expected policy success.